2015
DOI: 10.4048/jbc.2015.18.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Circular RNAs from Primary Kinase Transcripts in the Mammary Glands of Lactating Rats

Abstract: PurposeCircular RNAs (circRNAs), a novel class of RNAs, perform important functions in biological processes. However, the role of circRNAs in the mammary gland remains unknown. The present study is aimed at identifying and characterizing the circRNAs expressed in the mammary gland of lactating rats.MethodsDeep sequencing of RNase R-enriched rat lactating mammary gland samples was performed and circRNAs were predicted using a previously reported computational pipeline. Gene ontology terms of circRNA-producing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Investigators also declared the presence of protein kinases and their associated proteins among the specific genes encoding circRNAs. Interestingly, it is reported that four protein‐coding genomic regions as Rev3l, IGSF11, MAML2, and LPP that also transcribe elevated levels of circRNAs are involved in cancer (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators also declared the presence of protein kinases and their associated proteins among the specific genes encoding circRNAs. Interestingly, it is reported that four protein‐coding genomic regions as Rev3l, IGSF11, MAML2, and LPP that also transcribe elevated levels of circRNAs are involved in cancer (Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on circRNA microarray analysis have shown that multiple circRNAs are abnormally expressed in BC [20,21]. For example, a study performed by Tang et al has shown that 1,155 abnormally expressed circRNAs (715 down-regulated and 440 up-regulated) are present in BC tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study performed by Tang et al has shown that 1,155 abnormally expressed circRNAs (715 down-regulated and 440 up-regulated) are present in BC tissues [20]. A chip analysis conducted by Zhang et al has identified 1,314 abnormally expressed circRNAs, the majority of which are derived from coding genes Rev3l, IGSF11, MAML2, and LPP [21]. In this study, qRT-PCR and ISH confirmed that the expression of hsa_circ_0068033 was decreased in BC tissues and four BC cell lines, and this expression was associated with the clinical staging of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously detected the expression of thousands of circular RNAs in the mammary glands of a cow and a rat, with circHIPK3 present at a high abundance [14,15]. Interestingly, circHIPK3 has been reported to promote the proliferation of tumor cells, such as HuH-7, HCT-116, HeLa, PC-3, and DU145 cells [16][17][18].…”
Section: Introductionmentioning
confidence: 99%